2002
DOI: 10.1038/sj.ejhg.5200775
|View full text |Cite
|
Sign up to set email alerts
|

A human interstitial telomere associates in vivo with specific TRF2 and TIN2 proteins

Abstract: Mammalian telomeres are composed of long arrays of TTAGGG repeats that form a nucleoprotein complex which protects the chromosome ends. Human telomere function is known to require two TTAGGG repeat factors, TRF1 and TRF2, and several interacting proteins, but the mechanism by which the DNA/protein complex prevents end to end fusion in vivo has not been elucidated. In order to better understand the role of specific telomere-associated proteins in the organisation of chromosome ends, we have studied a patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…These nontelomeric functions might be, at least partially, explained by their binding to ITSs. Indeed, there is mounting indication that shelterin components can bind to interstitial DNA sequences: (i) TRF1 and TRF2 bind to the pericentromeric regions of hamster chromosomes containing large blocks of ITSs [23,24]; (ii) TRF2 and TIN2 bind to an ITS formed by a rare human chromosome rearrangement [25]; (iii) TRF2 binds to a stretch of telomeric sequence that is artificially inserted in the middle of the long arm of chromosome 4 [26]; (iv) Rap1 binds to several ITSs of the mouse genome [27]. However, three naturally occurring ITSs of human chromosomes do not appear to be bound by TRF2 [26].…”
Section: Thomas Simonet Et Al 1029mentioning
confidence: 99%
“…These nontelomeric functions might be, at least partially, explained by their binding to ITSs. Indeed, there is mounting indication that shelterin components can bind to interstitial DNA sequences: (i) TRF1 and TRF2 bind to the pericentromeric regions of hamster chromosomes containing large blocks of ITSs [23,24]; (ii) TRF2 and TIN2 bind to an ITS formed by a rare human chromosome rearrangement [25]; (iii) TRF2 binds to a stretch of telomeric sequence that is artificially inserted in the middle of the long arm of chromosome 4 [26]; (iv) Rap1 binds to several ITSs of the mouse genome [27]. However, three naturally occurring ITSs of human chromosomes do not appear to be bound by TRF2 [26].…”
Section: Thomas Simonet Et Al 1029mentioning
confidence: 99%
“…20 Fibroblasts were trypsinized, rinsed and resuspended in PBS (pH 7.2), but were then treated as the other cell types. Cells were centrifugated (300 t/min for 5 min) onto polylysine-coated slides in cytospin 3 (Shandon, Cergy-Pontoise, France), then fixed at room temperature (RT) for 10 min in 2% (w/v) paraformaldehyde/PBS (pH 7.2).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…20 After immunocytochemistry, all preparations were fixed with 1% (w/v) paraformaldehyde in PBS for 5 min, rinsed again before staining with DAPI (100 ng/ml) diluted in Vectashield (Vector Laboratories). All antibodies were tested in individual staining reactions for their specificity and performance.…”
Section: Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ITSs could also correspond to sites of spontaneous and induced chromosome breakage, conferring fragility to the region where they are inserted. At the molecular level, it has been shown that some proteins of the shelterin complex, such as TRF1, TRF2, and RAP1, can also locate to ITSs (Zakian 1995;Mignon-Ravix et al 2002;Krutilina et al 2003;Simonet et al 2011;Bosco and de Lange 2012), suggesting a role of these proteins in the organization and/or functioning of heterochromatic ITSs. In this sense, for example, the shelterin protein TRF1 is fundamental to preventing TTAGGG-repeat replication problems and protecting telomeres from breaking (Sfeir et al 2009).…”
mentioning
confidence: 99%